RELATIONSHIP OF EDUCATION, FAMILY INCOME, COMPLIANCE AND PROCEDURE CONSUMPTION OF IRON TABLET TO ANEMIA AMONG PREGNANT WOMEN - Septi Indah Permata Sari; Aris Noviani; Rr. Sri Nuriyaty Masdiputri; Nurul Inayah (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: In Indonesia, the contribution of anemia towards the maternal mortality is estimated to reach 10% up to 20%. Anemia may know as an initiating cause of various problems of infant and maternal mortality. Many ways have been done to overcome the case of anemia, but there are still so many pregnant women who suffer from anemia. Aims: This study aimed to identify therelationship of education level, family income, compliance and procedure of iron tablet consumption with anemia in pregnant woman atMidwifery Primary Care (MPC), Pakem, sleman, Yogyakarta. Methods: This was an observational analytic study with cross sectional design. The samples of this study were 39 pregnant mothers in MPC, who met the criteria inclusion and exclusion. The data was analyzed by chi-square test. Results: There were relationships between anemia and family income (p value = 0.042), compliance (p value = 0.017) and procedure of Iron tablet consumption (p value = 0.024). There was no relationship found between anemia on pregnant woman with education level (p value = 0.172). Conclusions: The research above indicates anemia in pregnancy is not caused by a single factor and should be treated as a matter of various causes. As well as for researchers next urged to conduct further research on the nutritional intake of pregnant women and infectious diseases to determine the factors that are directly related to the incidence of anemia among pregnant women.